Opportunities to develop multiple intelligences in the “communication and culture” section of the moet’s new english textbook 10 = Cơ hội để phát triển đa trí tuệ trong phần “giao tiếp và văn hóa” của SGK Tiếng Anh 10 (Thí điểm). - Nguyễn, Vân Thảo (2020)
The Theory of Multiple Intelligences has been of great interest to psychologists an deducators for its significant impact on language learning. However, this theory is still under-researched in Vietnamese context and there has been no published research on there presentation of multiple intelligences in English textbooks. Therefore, the purpose of this study is to investigate the “Communication and Culture” section of the New English Textbook 10 for the opportunities to develop multiple intelligences. All of the activities in chosen section of the Student Book were analyzed using a carefully designed MI check list based on relevant literature of the framework of the MI theory and existing studies on the MI in textbooks. The results show that the chosen section of the textbook mostly addressed verbal/linguistic, visual/spatial, interpersonal and logical/mathematical intelligences. The less common represented intelligences were intrapersonal, naturalist and musical intelligences. No instance of the bodily/kinesthetic intelligence was found in the analyzed activities. Hence, the opportunities to enhance linguistic, spatial, inter personal and logical intelligences are abundant while the chances for the other four intelligences are more limited. The findings of the study suggest that English teachers should fully exploit the textbook to help students develop different intelligences and consider the inclusion of more activities to develop the less developed intelligence types in the chosen section of the textbook in their lessons.